Tools for Teachers to Support Music Students in Managing and Coping With Their Workload in Higher Education - Jääskeläinen, Tuula; López-Íñiguez, Guadalupe (Frontiers in Education, 2022)
One-to-one tuition is an essential part of studying music and is appreciated by the music students. Problems can occur when there are diverse perceptions between teacher practice and student expectations. This study provides research-based evidence on 155 music students’ experiences of workload, stress, and coping in their interaction with teachers in higher education in Finland and the United Kingdom. The theoretical framework was informed by several theories in educational psychology research, such as the influence of teaching and learning environment on students’ perceived workload, and constructivist approach in teaching and learning music. The data included 155 music students’ open-ended answers in the questionnaire and interviews with 29 music students. The qualitative analysis was conducted through the methodological framework of transcendental phenomenology. The findings illustrate music students’ interaction with teachers concerning 1) the structure of students’ workload, 2) a music student’s individual workload, 3) workload relating to teaching and learning environments, and 4) psychological and physiological issues. A total of 43 constructive tools for teachers were created based on these music students’ experiences. These tools are based on the constructivist principles focusing on the music students’ knowledge and capabilities and they can be utilized to better support students in managing and coping with their workload and stress in higher music education institutions.